POLA HUBUNGAN PATRON- KLIEN PADA KOMUNITAS NELAYAN DI KELURAHAN MALABRO KECAMATAN TELUK SEGARA KOTA BENGKULU - Sinaga, Herman; Widiono, Septri; Irnad, Irnad (Jurnal AGRISEP, 2015)
This research aimed to describe the characteristic of fishing activities in Malabro Municipal, Teluk Segara District, Bengkulu city and to describe the pattern of patronclient relationship between wholesaler, vessel owner and fishermen. This researh conducted using qualitative method. Data collected using obsevation, interview, and documantes information related to this research. Thi result shows that fishermen are using three fishing tools, such as gillnets, payang and trammel nets. These fishing tools will be influence many things like type of vessel, amount of fishermen, and production sharing system. In patron-client relations between wholesaler and boat owner. Wholesaler has a role as patron and the boat owner has a role as client. Patron-client relation is mutual benefit. While, relation between wholesaler or vessel owner and fishermen hasn’t shown patron- client relationship but only shown relation of fishing activities.